Enhancing the Capacity of CLC Teachers in Tawau, Sabah, Malaysia to Innovate Game-Based Digital Assessment - Nisa Arafiyah Tri Wulandari; Monika Handayani; Maya Puspitasari; Rika Aprianti; Nova Tri Prasetyo; Aiza Sunarto; Mad Noor Madjapuni (SPEKTA (Jurnal Pengabdian Kepada Masyarakat : Teknologi dan Aplikasi), 2026)
Background: This community service program aimed to address gaps in digital assessment literacy among Community Learning Center (CLC) teachers in Tawau, Sabah, Malaysia, and to support more engaging assessment practices in low-resource educational settings. Contribution: The program enhanced teachers’ practical capacity to design and implement game-based digital assessments and provided limited infrastructure support to improve the feasibility of sustained use in CLC classrooms. Method: The program was designed using the Community Tool Box framework, emphasizing community needs assessment and an evaluation plan. It was delivered through two modes: an online training session and an in-person workshop. Results: The online training involved 117 educators from multiple CLCs across Sabah, followed by an in-person workshop with approximately 100 teachers in Tawau. Participants produced or designed game-based digital assessment activities using Blooket as a hands-on output, and post-program support included educational grants (projectors, laptops, and a Blooket Plus account) to strengthen implementation sustainability. Conclusion: The two-mode training model produced concrete assessment outputs and strengthened readiness to integrate game-based digital assessment in CLC contexts. Future work should extend evaluation toward classroom-level impact and test replication across CLC districts with varying resource constraints.